Occurrence and co-occurrence of hallucinations by modality in schizophrenia-spectrum disorders. (June 2017) - McCarthy-Jones, Simon; Smailes, David; Corvin, Aiden; Gill, Michael; Morris, Derek W.; Dinan, Timothy G.; Murphy, Kieran C.; Anthony O′Neill, F.; Waddington, John L.; Australian Schizophrenia Research Bank,; Donohoe, Gary; Dudley, Robert
Abstract: It is not only unclear why hallucinations in schizophrenia occur with different prevalence by modality, but also to what extent they do. Reliable prevalence estimates of hallucinations by modality in schizophrenia are currently lacking, particularly for non-auditory hallucinations. Studies have also tended to report lifetime, not point prevalence by modality. This study assessed the prevalence and co-occurrence of hallucinations, for both lifetime and point prevalence, across the auditory, visual, olfactory, and tactile modalities, in people diagnosed with chronic schizophrenia-spectrum disorders in Ireland (N=693) and Australia (N=218). Lifetime prevalence was 64–80% auditory, 23–31% visual, 9–19% tactile, and 6–10% olfactory. Past month prevalence was 23–27% auditory, 5–8% visual, 4–7% tactile, and 2% olfactory. The majority of participants had only hallucinated in one modality, with this nearly always being the auditory. Approximately one-third had hallucinated in two modalities, most commonly the auditory and visual. Most currently hallucinating patients also hallucinated in a single modality, again, nearly always the auditory. Whereas 30–37% of patients with lifetime auditory hallucinations had experienced visual hallucinations, 83–97% of patients with experience of visual hallucinations had experienced auditory hallucinations. These findings help delineate the modality distribution of hallucinations in schizophrenia, and provide an explanatory target for theoretical models. Highlights: We consider why hallucinations in different modalities occur at different rates. We examined rates of auditory, visual, tactile and olfactory hallucinations. Lifetime and current prevalence were reported in two large samples. Auditory hallucinations were more common than visual and then tactile, then olfactory. Auditory hallucinations without visual were common but the opposite was rare.